Designing Educational Board Games For Children On Snake Handling Using Competitive Mechanisms - Josefin Oktaviane; Jasson Prestiliano; T. Arie Setiawan Prasida (Indonesian Journal Of Educational Research and Review, 2021)
Education with material and only listening to explanations make some people bored so that the information they want to convey is not well received. In addition, there is a lack of media that can educate snake handling and facilitate children in learning in a fun way and can be played outside of study hours. This study aims to analyze an educational board game for snake handling using competitive mechanisms in children. This research uses a descriptive method. The techniques used in collecting data are interviews, observations, and questionnaires. The instrument used to collect data is a questionnaire. Sources of data obtained from previous studies, online articles, and interviews will be analyzed descriptively. Based on the results of data analysis, the board game as an educational media about the basic handling of snakes has a positive impact on the target. 80% of the targets who do not understand handling snakes and other types of snakes understand and enjoy the education implemented in the board game media. It can be concluded that educational board games can educate children about snake handling using competitive mechanisms.